Job Market Prospects of Breast vs. Prostate Cancer Survivors in the US: A Double Hurdle Model of Ethnic Disparities - Shelley I. White-Means; Ahmad Reshad Osmani (Journal of Family and Economic Issues, 2019)
Labor market presence of cancer survivors has been significantly improved as medical technology revolutionized cancer-specific diagnoses and treatments. However, less understood are post-cancer variations in job market outcomes of racial and ethnic minorities in the US. Using a theoretical framework derived from family labor supply decision models and taking advantage of the rich data in the 2008–2014 Medical Expenditure Panel Survey (MEPS), this study employs a double-hurdle empirical model of labor force participation and hours worked to evaluate the employment decisions of Black and Hispanic cancer survivors. Hispanic and Black breast cancer survivors were less likely to be employed by 4% and 7.5%, respectively, when compared with Whites. Black prostate cancer survivors were 8% less likely to work than Whites, with nonsignificant differences between Hispanic and White prostate cancer survivors. Once employed, Black and Hispanic breast cancer survivors worked an extra 4 and 6 h than Whites, while Hispanic prostate cancer survivors worked 5 fewer weekly hours than Whites. In addition, our estimates indicate the significance of job types in labor market outcomes post-cancer. Employment of minorities in blue collar or service occupations decreased employment hours of survivors. Labor market disparities for minorities amplifies the socio-economic and familial burden of cancers. This timely work motivates informed public policy to reduce unexamined consequences of chronic conditions among minorities.
Keywords: J15; J22; 330; Employment disparities; Breast cancer